The Effect of Using Silver Fiber Content Yarns in Shirting Fabrics on Abrasion Resistance and Pilling Properties. Issue 11 (2nd November 2022) - Kaynar Taşcı, Zehra; Çelik, Nihat
ABSTRACT: In the study, shirting satin fabrics were produced using 100% cotton yarn and using yarns containing different proportions of silver fiber. The effect of silver fiber, which is used to gain antibacterial properties to shirting fabrics, on the pilling and abrasion resistance of fabrics were investigated. It is determined that even fabrics containing a small amount of silver fiber have very good antibacterial properties. It is concluded that the pilling behavior of the fabrics containing silver fiber compared to the reference fabric varies but is not affected by the increase in the silver fiber ratio in the fabric. The change of silver fiber ratio in the fabrics did not have a significant effect on the abrasion resistance.